'Box‐Profile' Ion Implants as Geochemical Reference Materials for Electron Probe Microanalysis and Secondary Ion Mass Spectrometry. Issue 4 (27th July 2019) - Wu, Haosheng; Böttger, Roman; Couffignal, Frédéric; Gutzmer, Jens; Krause, Joachim; Munnik, Frans; Renno, Axel D.; Hübner, René; Wiedenbeck, Michael; Ziegenrücker, René
Abstract : Although electron probe microanalysis and secondary ion mass spectrometry are widely used analytical techniques for geochemical and mineralogical applications, metrologically rigorous quantification remains a major challenge for these methods. Secondary ion mass spectrometry (SIMS) in particular is a matrix‐sensitive method, and the use of matrix‐matched reference materials (RMs) is essential to avoid significant analytical bias. A major problem is that the number of available RMs for SIMS is extremely small compared with the needs of analysts. One approach for the production of matrix‐specific RMs is the use of high‐energy ion implantation that introduces a known amount of a selected isotope into a material. We chose the more elaborate way of implanting a so‐called 'box‐profile' to generate a quasi‐homogeneous concentration of the implanted isotope in three dimensions, which allows RMs not only to be used for ion beam analysis but also makes them suitable for EPMA. For proof of concept, we used the thoroughly studied mineralogically and chemically 'simple' SiO2 system. We implanted either 47 Ti or 48 Ti into synthetic, ultra‐high‐purity silica glass. Several 'box‐profiles' with mass fractions between 10 and 1000 μg g −1 Ti and maximum depths of homogeneous Ti distribution between 200 nm and 3 μm were produced at the Institute of Ion Beam Physics and Materials Research of Helmholtz‐Zentrum Dresden‐Rossendorf. Multiple implantation steps using varying ion energies and ion doses were simulated with Stopping and Range of Ions in Matter (SRIM) software, optimising for the target concentrations, implantation depths and technical limits of the implanter. We characterised several implant test samples having different concentrations and maximum implantation depths by means of SIMS and other analytical techniques. The results show that the implant samples are suitable for use as reference materials for SIMS measurements. The multi‐energy ion implantation technique also appears to be a promising procedure for the production of EPMA‐suitable reference materials. Key Points: Homogeneous (x, y and z) geochemical references materials can be produced by multi‐energy ion implantation. First quantification results are promising. 'Box‐profile' implants are suitable for use as reference materials for SIMS measurements. The multi‐energy ion implantation technique has the potential to produce EPMA‐suitable reference materials.